Preparation of carboxylated graphene oxide nanosheets/polysulphone hollow fibre separation membranes with improved separation and dye adsorption properties. (10th July 2019) - Shi, Wenying; Zeng, Xianhua; Li, Hongbin; Zhou, Rong; Zhang, Haixia; Qin, Xiaohong
Abstract: Novel hollow fibre polysulphone (PSF) separation membranes were prepared via the incorporation of carboxylated graphene oxide (cGO) in membrane matrix during the dry‐wet spinning process to improve the membrane performance of water flux and dye adsorption. The surface composition and morphology of the prepared cGO‐incorporated hollow fibre membranes were characterised by means of Fourier Transform–infrared spectra and scanning electron microscopy. The effects of different cGO contents on membrane surface hydrophilicity, separation performance, anti‐compaction and adsorption properties were investigated through measurements of the water contact angle, cross‐flow filtration and methylene blue (MB) adsorption experiments. The results demonstrated that the cGO‐incorporated membranes had more hydrophilic surfaces, higher permeation flux, better anti‐compaction properties and a higher adsorption rate of MB than that of the PSF control membrane. When cGO content was 0.45 wt.%, the pure water flux of the modified membrane increased from 90.56 to 148.26 l m −2 h −1 at 0.1 MPa; also, rejections of bovine serum albumin and polyethylene glycol (PEG‐20000) maintained relatively high values of 98.81 and 93.89%, respectively. The incorporation of cGO nanosheets could effectively improve membrane anti‐compaction properties and the adsorption rate of MB.